Temporal and Spatial Characterization of Mononuclear Phagocytes in Circulating, Pulmonary Alveolar, and Interstitial Compartments in LPS-Induced Acute Lung Injury - Li, Qi; Xiang, Guoan; Peng, Shouchun; Ji, Wenjie (Frontiers in Surgery, 2022)
Peripheral circulating monocytes and resident macrophages are heterogeneous effector cells that play a critical role in the maintenance and restoration of pulmonary integrity. However, their detailed dynamic changes in lipopolysaccharide (LPS)-induced acute lung injury (ALI) remain unclear. Here, we investigated the impact of mononuclear phagocyte cells in the development of LPS-induced ALI/Acute respiratory distress syndrome (ARDS) and described the relations between the dynamic phenotypic changes and pulmonary pathological evolution. In this study, mice were divided into two groups and intraperitoneally injected with normal saline (NS) or LPS, respectively. A series of flow cytometry assay was performed for the quantification of peripheral circulating monocyte subpopulations, detection of the polarization state of bronchoalveolar lavage fluid (BALF)-isolated alveolar macrophages (AMϕ) and pulmonary interstitial macrophages (IMϕ) separated from lung tissues. Circulating Ly6Clo monocytes expanded rapidly after the LPS challenge on day 1 and then decreased to day 7, while Ly6Chi monocytes gradually increased and returned to normal level on the 7th day. Furthermore, the expansion of M2-like AMϕ (CD64+CD206+) was peaked on day 1 and remained high on the third day, while the polarization state of IMϕ (CD64+ CD11b+) was not influenced by the LPS challenge at all the time points. Taken together, our findings show that Ly6Clo monocytes and M2-like AMϕ form the major peripheral circulation and pulmonary immune cell populations, respectively. The dynamic changes of mononuclear phagocyte in three compartments after the LPS challenge may provide novel protective strategies for mononuclear phagocytes.